Can we replace toxicants, achieve biosecurity, and generate market position with semiochemicals? - Suckling, David M. (Frontiers in Ecology and Evolution, 2015)
Biosecurity covers both long-term management of existing pests and the urgent government responses to alien invasive species which have yet to become fully established. Mating disruption, mass trapping and lure and kill systems all have potential to be used in pest management and against new incursions of certain types of organisms, predominantly moths and beetles. Straight chained lepidopteran sex pheromones have emerged as a source of potential market advantage in pest management, with trapping systems and residue-free multiple species disruption systems being increasingly adopted to reduce insecticide use and meet private stabndard. Semiochemicals can also offer new surveillance tools in pre-border biosecurity, greatly improving the chances for successful eradication of alien invasive species. However, a rising frequency of incursions of alien invasive species and consequent rise in official eradication programs due to globalisation points strongly to the need for further investment in the areas of discovery and development of surveillance and eradication technologies, from a sound knowledge of chemical ecology.